Atrial fibrillation in endurance-trained athletes - Sorokin, A. V.; Araujo, C. G. S.; Zweibel, S.; Thompson, P. D. (British Journal of Sports Medicine, 2011)
Background Endurance exercise training produces multiple cardiac adaptations including changes in electrophysiological function that may make endurance-trained athletes more vulnerable to atrial fibrillation (AF). This possible association is not recognised by many practising cardiologists and sports physicians. Consequently, we performed a literature review to examine the relationship between atrial fibrillation and endurance exercise training among athletes. PubMed was searched from January 1960 through December 2008 to identify articles examining the relationship between endurance exercise training and AF.